Assessment of Selected Trunk and Neck Muscle Activity in Children with Idiopathic Toe Walking - Iwona Wilk; Marcin Piwecki; Krzysztof Kassolik; Donata Kurpas (Rehabilitacja Medyczna)
Introduction: Analyses related to idiopathic toe walking (ITW) are limited to the functioning of the lower-limb. It is recommended to broaden our understanding and consider other parts of the body in accordance with the principles of tensegrity.Objectives: The purpose of this study is to assess the activity of selected trunk and neck muscles in children with ITW.Material and methods: The study involved 50 children (7-10 years old). They were divided into a study group (SG): children with ITW (n=20); and a control group (CG): healthy children (n=30). The static and dynamic activity of the cervical and lumbar parts of erector spinae muscle (CES and LES, respectively) and of the sternocleidomastoid muscles was measured by sEMG. Measurements were performed on both sides of the body.Results: Statistically significant differences between SG and CG were found in the muscle activity of CES on both sides of the body with regard to statics in the neutral position (p<0.001). Differences were observed in the activity of LES between groups in statics for the neutral, hyperextension and flexion-relaxation positions on both sides of the body (p<0.001). In dynamics, statistically significant differences between groups were found: on the left and right sides of the LES in flexion, extension and rotation on the left side (p<0.05), on the left and right sides for the CES in extension, flexion on the right side, rotation on the right and left sides (p<0.05), and for the SCM, in extension and rotation on the left side (p<0.05).Conclusions: Children with ITW have disturbed tone of the trunk and neck muscles. It is advised that, apart from the ankle joints and muscles of the lower limb, physiotherapy be extended to the back and neck muscles.